Designing dynamically "signature business model" that support durable competitive advantage - Andrejs Čirjevskis (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Purpose/Research question: The paper provides an empirical research of the Samsung case. In particular, we study the case by adopting three frameworks: dynamic capabilities (DC, examined by using the sensing/seizing/transforming approach), business model (BM, examined by using the BM canvas), and customer value proposition (CVP), examined by using the PERFA ((Performance, Ease of use, Reliability, Flexibility, and Affectivity) framework. The aim is to demonstrate that three frameworks successfully explain Samsung competitive advantage. Research question has been defined as follows: how dynamic capabilities actually operate in Samsung Group and contribute to its competitive advantage? Key literature reviews: Dynamic capabilities enable a firm to identify and orchestrate the necessary resources for designing and implementing a business model that will, if employed in conjunction with a good strategy, be associated with high levels of sustainable profits. The selection/design of business models is a key micro foundation of dynamic capabilities - the sensing, seizing, and reconfiguring skills that the business enterprise needs if it is to stay in synch with changing market. However, there are few examples how successful ICT industry players design dynamically their "signature business model" by Teece (The Academy of Management Perspectives 28:(4)328-352, 2014) that can support durable competitive advantage. Design/Methodology/Approach: This proposed research seeks to explore critical aspects pertaining micro foundations of DC. In this research, two stages of research work will be involved. The first stage is deductive case studies research. We relied on an extensive archival search that included financial statements, annual reports, internal documents, industry publications, and CEO statements to get at a micro-level understanding (Barr et al., 1992), that really boosts our data and better understanding of micro foundation of DC. The second stage involves a demonstration of development process of new conceptual model of research. Findings/Results: The research question of current paper has been answered empirically by using data of world leading ICT industry: Samsung Group. What we can learn beyond the ICT industry context from our analysis in terms of generalization of our research results is that the synchronization of business models with the business environment is a critical role of dynamic capabilities in successful organizations. The conversion of value delivered to the customer into value captured by the enterprise is arguably the essence of a business model. Research limitations/Implications: We carried out qualitative research of huge secondary data source that help us make sense of the casual links that connect DC, BM and CVP. We didn't interview executives of those companies due to availability of actual interviews as a secondary data sources. Our contribution is a new conceptual model of competitive advantage paradigm as a product of dynamic capabilities, business models and customer value proposition. The paper also provides analysis, which could be productively used for a case study discussion in class.
Keywords: 650; Dynamic capabilities; Business model; Customer value proposition